Learn Arabic Grammar Via The Arabic-VR Application - Awang Ali, Mohammad Amnan; Md Ghalib, Mohd. Feham; Hussin, Muhammad Hafizuddin; Abdul Rahim, Abdul Hadi (USIM, 2024)
This research aims and focuses on a novel approach to learning Arabic grammar through the Arabic-VR application using VR technology and to gather students’ perspectives about their needs on form – hence, developing the application using VR technology in learning Arabic grammar. This study is based on the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) instructional design model and employs the Design and Developmental Research (DDR) approach. Based on this approach, this study is divided into three main phases: the first phase (the needs analysis phase), the second phase (the design and development phase), and the third phase (the evaluation phase). This Arabic-VR application is currently undergoing testing and will be released as a mobile-VR application in the future. The first phase involves a questionnaire survey on the use of the application, issues regarding students’ motivation and attitudes towards learning Arabic grammar, as well as knowledge and needs of using the application including the interface and features of the application and conducted on 150 students who are involved in an Arabic language subject (subject code: DTU 2022) as a compulsory subject at the Centre for Languages & General Studies, KUIPs. The purpose is to see the need for the development of the Arabic-VR application. The data was by descriptive statistics using the Statistical Package for the Social Science (SPSS) software to find the percentages, mean scores, and standard deviation. Findings revealed a high need to develop the Arabic-VR application for learning Arabic grammar. There is a positive response to adopting technological tools i.e. VR technology for language learning as it increases students’ motivation, purpose, and attitudes toward learning Arabic grammar. This initiative will have a big impact on future Arabic language acquisition. This study will improve students’ grasp of Arabic and their attitudes about the language.